IMPLEMENTASI PENGONTROLAN TEGANGAN KELUARAN DC STEP UP QUADRATIC BOOST CONVERTER DENGAN VARIASI TEGANGAN INPUT DARI SINGLE PV MENGGUNAKAN LOGIKA FUZZY - Irwan Mahmudi; Jumiyatun Jumiyatun; Kadri Kadri (Foristek, 2020)
Resulting output voltage is not constant due to light intensity and surface temperature of the solar panels. To overcome the output voltage of solar panels that tends to fluctuate, is to add a DC-DC converter to the output side of the DC-DC Converter used in this study is the Quadratic Boost Converter type which has a role to increase the output voltage of the monocrystalline type solar panel so that it remains constant at 24V DC. using Mamdani Fuzzy Logic Control as a method of controlling PWM switching. The results obtained from this study are that the quadratic boost converter can keep the output voltage of the solar panel constant at 24V, with low ripple voltage and overshoot. The Mamdani fuzzy logic method used can produce a constant output voltage value with a rise time of ± 5 seconds. The efficiency obtained from this converter hardware is quite good, ranging from 76% - 88%.